Biochemical response to sport related anxiety : Biokemijski odgovor na anksioznost uzrokovanu sportskim aktivnostima - Dinter, Sandra (Array, 2021)
The goal of each professional athlete is to reach maximal performance. In order to achieve that, physical as well as mental training needs to be part of a regular training routine. Anxiety significantly affects athletic performance while extreme anxiety levels are associated with reduced athletic achievements. Therefore, controlling sport-related anxiety seems to be one of the most significant aspects for elite athletes. In order to understand the biology behind sport-related anxiety, this review is focused on the biochemical responses to such a stressor. Knowing the biochemistry of stress and its limiting factors on athletic performance enables us a greater understanding of the influence of anxiety on professional athletes. It might help to better understand the importance of sport psychology and how our mindset influences our performance. Furthermore, the correlation between the placebo effect and the manner in which the mind controls the body are considered as it might prove an important tool for future athletic training and sport psychology.